Award for palm oil pressing machinery manufacturer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The artisanal palm oil pressing machine named 'Caltech' recently received an award from the jury of 'Afrique Expansion' for 1986. This pressing machine is suitable for small farmers who may possess some hundreds of wild palm trees or only a few...